PENGARUH KELENGKAPAN DATA UNIT CASEMIX TERHADAP KETEPATAN WAKTU PROSES KLAIM BPJS KESEHATAN DI RUMAH SAKIT GLADIS MEDICAL CENTER - Rizky Aprilianti Lestari; Windi Pertiwi; M. Nabil Fahmi; Zahra Assyifa; Pinka Septia Maharani (Journal of Hospital Administration and Excellent Health Service, 2026)
The Casemix Unit plays a crucial role in ensuring the completeness of BPJS Kesehatan claim documents. Delays in data completion can hamper the verification and claim submission process, resulting in delays in claim payments, disruptions to cash flow, and hospital operations. Therefore, research is needed to analyze the effect of delays in data completion on the timeliness of BPJS Kesehatan claim processing. This study aims to analyze the effect of delays in data completion in the Casemix Unit on the timeliness of BPJS Kesehatan claim processing at Gladis Medical Center Hospital. Risk management, hospitals, Opportunity Solution Tree, Fishbone Analysis, qualitative research. This research is a quantitative analytical study with a cross-sectional approach. The study population is all BPJS Kesehatan claim files processed at the Casemix Unit of Gladis Medical Center Hospital during the study period. The sample was determined using a total sampling technique. Data were obtained through document observation and claim file completeness checklists. Data analysis was performed univariately to describe the characteristics of the variables, and bivariately using the Chi-Square test with a 95% significance level (α = 0.05). The results showed that the majority of delays in the BPJS Kesehatan claims process were caused by delays in data completion at the Casemix Unit. The bivariate analysis revealed a significant correlation between delays in data completion and the timeliness of BPJS Kesehatan claims processing (p<0.05). The higher the level of delay in data completion, the greater the risk of claims processing delays. Hospitals need to improve coordination between units, strengthen compliance with complete medical record documentation, and optimize information systems to support a more effective and efficient claims process.